Sistem Monitoring Volume Dan Gas Sampah Menggunakan Metode Real Time Operating System (RTOS) - Tugar Aris Andika Prastiyo Raharjo; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Rubbish is things that can't be used anymore and it is usually dirty and smelly. A pack of rubbishes in trash bin produce gasses that can give bad impacts to health, like methane (CH4), ammonia (NH3), and hydrogen sulphide (H2S). If the methane concentration is too high, then it will cause asphyxiation and fire. Besides that, rubbish volume also should be noticed because it can cause uncomfortable environment condition if the rubbish has exceeded the volume of trash bin. This research will design a technology system which can help the owner of trash bin to know the trash bin condition in real time and continuously. That system observes the rubbish volume and gases produced by sensors of NH3, CH4, H2S and infrared E18-DN80NK, by using Real Time Operating System (RTOS). RTOS is used as one of the sensor readings and delivery tasks that are handled by the microcontroller in real-time. From the results of 10x testing done on the rotten garbage is known to read the sensor MQ-135 has an average ammonia level of 35.71 PPM, MQ-4 has a methane content of 293.5 PPM, TGS2602 has 9.738 PPM of hydrogen sulphide and Infrared E18-DN80NK sensor can detect the height of the waste by output above the threshold (waste exceeds the sensor limit) and below threshold when the waste has not exceeded the sensor limit. So the level of gas produced by waste is methane gas.